Intercorrelation among MOC1, MOC3, and TN1 Gene Expressions with the Architecture of Five Rice Genotypes - Afridha Sari; Miftahul Huda Fendiyanto; M. Miftahudin (HAYATI Journal of Biosciences, 2026)
Tillering is an important rice characteristic that determines the architecture of the rice plant and affects yields. MONOCULM 1 protein encoded by the MOC1 gene interacts with MOC3 protein to influence axillary meristem formation and promote tillering. TILLER NUMBER 1 protein encoded by the TN1 gene to inhibit rice tillering. This study aimed to analyze the expression of tillering regulatory genes MOC1, MOC3, and TN1 in five rice genotypes based on their morphological characteristics. RNA was isolated at the pre tillering and tillering stages. Gene expression was analyzed using RT-PCR. The results showed that Hawara Bunar and Landeo rice produced fewer tillers (3-5) than IR64, Towuti, and Tukad Petanu (7-9). Although the number of tillers was lower, the grain weight produced by the Hawara Bunar rice cultivar was higher than that of the other four rice cultivars. The formation of a few tillers in Hawara Bunar and Landeo rice was influenced by low expression of the tiller regulatory genes MOC1 and MOC3 and by high expression of the TN1 gene, which inhibits tiller formation. These findings reveal a novel relationship between the expression of MOC1, MOC3, and TN1 genes and tiller formation, highlighting Hawara Bunar as a promising breeding line for rice with ideal plant architecture.